Initial public offerings and pricing anomalies / Leow Hon Wei - Leow , Hon Wei (2020)
Initial Public Offering (IPO) is a form of fundraising through the stock market of which has evolved as an essential platform to study the performance of newly issued shares. In the case of an emerging market like Malaysia, the pricing anomalies that measure the performance of initial return and flipping activity of IPO remain an interesting subject. During the period of Global Financial Crisis (GFC) in 2008-09, it is believed that the market sentiment will affect the initial return of new IPO and oversubscription will be negative, and hence firms will be unwilling to do the new listing on the stock market. However, results from our first paper show that oversubscription is positive and initial return is not necessarily negative. The results dispel the notion that investors should totally shun IPO during crisis period as there are still positive initial returns (offer-to-close) and initial returns (high-low intraday) among the new issues. Next, the second paper of the first three-day initial return shows that there is a positive relationship between the oversubscription ratio and initial return and negative relationship between trading volume and initial return on the first trading day. However, the relationship does not exist on the second and third day of trading. In addition, the trading volume does not act as a moderator that worsens the relationship between oversubscription ratio and initial return. This shows that investors should actively participate in subsequent trading of an IPO. This is because higher participation will bring greater shareholder wealth in the stock market. The third paper touches on flipping activity and heuristic representation, the results show: firstly, the oversubscription ratio has a positive relationship with flipping activity. This is because higher demand makes investors flip more to liquidate the IPO on the first trading day. In contrast, firm size has a negative relationship with flipping activity. Larger IPO firm is more stable in terms of performance, and less risky in terms of business operation; Secondly, heuristic representation influences the relationship between oversubscription ratio and flipping activity. This study dispels the notion that investors who are active in subsequent trading but not necessarily obtain a profit from the liquidation. Lastly, this thesis explores the IPO of newly established Special Purpose Acquisition Companies (SPACs). If SPACs are liquidated properly, it shows that the SPAC is a workable model for a new listing framework. Shareholders will get back their money and future investors feel comfortable with the fact that the system works. On the contrary, if the policy maker allows an extension for those SPACs which fail to acquire new qualifying assets, it would destroy the market confidence. In conclusion, industry players reckon that SPACs still have a bright future through its controlled experiment, stringent measurement and effective built-in mechanism with numerous safeguards to the processes of SPAC IPOs. In short, this thesis has examined and published the findings of IPOs and contributed to the extant literature of IPOs in the context of emerging markets.